10 - Diagnostic du système éducatif béninois: Eléments pour une réforme novatrice des systèmes éducatifs africains: by Dénis Amoussou-Yeye - Dénis Amoussou-Yeye (Africa Development, 1994)
An evaluation of Benin education system reveals that the system has a poor internal and external efficiency as is shown by the tow rate of successful candidates, the high rates of dropouts and unsuccessful candidates in primary and secondary cycles as well as the growing number of unemployed diploma holders. The crisis is exacerbated by a growing demographic pressure The author makes suggestions as to how to improve the system His argument is that syllabuses for secondary and university education should be professionalised and that there should be more adequacy between the Benin education system and the objectives of political, economic and social development.